“Desperate times, desperate measures”: an appraisal on Vietnamese law’s limitation of rights in the COVID-19 crisis - Kien Tran; Khoi Trong Dao (Cogent Social Sciences)
This research is a pioneering attempt to comprehensively analyze the responses of Vietnamese human rights law to the challenges posed by Covid-19. Using conventional, trusted legal research methods, most notably desk review of legislation and case law analysis, this research affirms that this pandemic once again continually demonstrates the significance of limitation of rights doctrines to human rights protection in the most extreme conditions. In the case of Vietnam, many anti-epidemic measures, although highly efficacious in epidemic prevention, have placed immense and disproportionate restrictions on constitutional rights. While several limitations of rights doctrines in international human rights law have been partially recognized in Vietnamese law, the internalization, clarification, and application of these doctrines still face notable difficulties in practice, hindering the protection of rights when Covid-19 occurs. The article then suggests proposals to concretize the boundaries and conditions of the limitation of rights and criteria for balancing the stakeholders’ interests to improve Vietnamese human rights law, with implications for similar developing and transition jurisdictions’ legislative processes.